Gentrification Processes in the Frankfurt Ostend District: Municipal Neighbourhood Upgrading Strategies and the Relocation of the European Central Bank - Mösgen, Andrea; Schipper, Sebastian (Raumforschung und Raumordnung | Spatial Research and Planning, 2017)
The centrally located Ostend district in Frankfurt am Main had provided space for the lower-rent housing segment in particular since the 1950s and was therefore characterised by below-average rent price and real-estate value trends. Because these trends have reversed starting in the mid-2000s, this paper analyses at first the extent to which the Ostend district is impacted by gentrification. Secondary statistical sources show an exclusionary process of displacement in this former working class neighbourhood, which had led, during the last fifteen years, to a slow but clearly distinguishable change in the social structure favouring higher income groups. In a second step we analyse how the City of Frankfurt was able to upgrade the Ostend district – something that many had considered impossible. Through an analysis of municipal documents and publications we argue that municipal decision makers have used various tools for enabling and supporting the gentrification of this district since the 1980s. The subsequent displacement processes were accelerated by the 2002 decision to relocate the headquarters of the European Central Bank (ECB) to the Ostend district. Using discourse analysis we show that the relocation decision has led to a distinctive symbolic valorization of the district.